2005
DOI: 10.1124/jpet.105.097782
|View full text |Cite
|
Sign up to set email alerts
|

9L Gliosarcoma Cell Proliferation and Tumor Growth in Rats Are Suppressed by N-Hydroxy-N′-(4-butyl-2-methylphenol) Formamidine (HET0016), a Selective Inhibitor of CYP4A

Abstract: The present study examined the effects of N-hydroxy-NЈ-(4-butyl-2 methylphenyl) formamidine (HET0016), a selective inhibitor of the formation of 20-hydroxyeicosatrienoic acid (20-HETE) on the growth of 9L rat gliosarcoma cells in vitro and in vivo. After 48 h of incubation, HET0016 reduced the proliferation of 9L in vitro by 55%, and this was associated with a fall in p42/p44 mitogen-activated protein kinase and stress-activated protein kinase/c-Jun NH 2 -terminal kinase phosphorylation and increased apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
54
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 25 publications
7
54
0
1
Order By: Relevance
“…Guo et al (14) described proliferative, but not antiapoptotic effects of 20-HETE mediated by VEGF in human dermal microvascular cells. In a separate study, however, this group reported antiproliferative effects of HET0016 (an inhibitor of the formation of 20-HETE) in gliosarcoma cells in vivo and in vitro (15). Our studies support a pro-proliferative effect of 20-HETE in BPAECs, but we focused on the mechanisms through which this lipid promotes survival in these cells.…”
Section: Discussionmentioning
confidence: 51%
“…Guo et al (14) described proliferative, but not antiapoptotic effects of 20-HETE mediated by VEGF in human dermal microvascular cells. In a separate study, however, this group reported antiproliferative effects of HET0016 (an inhibitor of the formation of 20-HETE) in gliosarcoma cells in vivo and in vitro (15). Our studies support a pro-proliferative effect of 20-HETE in BPAECs, but we focused on the mechanisms through which this lipid promotes survival in these cells.…”
Section: Discussionmentioning
confidence: 51%
“…Proliferation studies were performed as described previously (Guo et al, , 2006. EPCs were incubated with VEGF (20 ng/ml) or 20-HETE (1 M) for 48 h. In some experiments, the cultures were exposed to VEGF in the presence of 10 M N-hydroxy-NЈ-(4-butyl-2-methylphenyl)formamidine (HET0016), a selective inhibitor of 20-HETE synthesis.…”
Section: Isolation and In Vitro Culture Of Ac133mentioning
confidence: 99%
“…We and others found that inhibition of 20-HETE synthesis reduced ERK1/2 activation (9,10,28,29), but the mechanism by which 20-HETE stimulated this protein complex remains to be established. Studies have implicated an interaction between receptor and nonreceptor tyrosine kinases to mediate the functions of 20-HETE in the kidney (7,39).…”
mentioning
confidence: 99%
“…These tyrosine kinases, specifically EGF receptor (EGFR), are known to play an important role in mediating growth and cell proliferation through the activation of the Raf/MEK/ERK pathway in PKD and various epithelial cancers (22,33,40,46). To further validate the potential interaction of 20-HETE with tyrosine kinases, recent studies showed that inhibition of 20-HETE synthesis reduced EGFR activation, which was associated with reduced proliferative activity (9,10,28).…”
mentioning
confidence: 99%